2009
DOI: 10.1038/ejcn.2009.101
|View full text |Cite
|
Sign up to set email alerts
|

Associations between gender, age and waist circumference

Abstract: In December 2008, the World Health Organization (WHO) convened a consultation to discuss cut-points for waist circumference (WC). As part of that effort, this paper examines the impact of gender and age on WC. As WC is influenced by body weight, body composition and fat distribution, their associations with gender and age were reviewed. We also noted the relationships with sex hormones, parity and menopause. We then summarized data on gender, age and WC. This presentation is not intended to be comprehensive, b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

23
151
4
8

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 258 publications
(194 citation statements)
references
References 59 publications
(73 reference statements)
23
151
4
8
Order By: Relevance
“…Both the mean values and the percentile distributions indicate that peripheral fat deposits remain higher in women than in men at all ages. This probably relates to gender differences in body composition, and adipose tissue distribution in particular, attributable to the influence of sex steroid hormones [22]. This may be important because several studies have shown an association between leg fat deposits and glucose metabolism, lipid profiles, blood pressure, and risk factors for CVD [23,24].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Both the mean values and the percentile distributions indicate that peripheral fat deposits remain higher in women than in men at all ages. This probably relates to gender differences in body composition, and adipose tissue distribution in particular, attributable to the influence of sex steroid hormones [22]. This may be important because several studies have shown an association between leg fat deposits and glucose metabolism, lipid profiles, blood pressure, and risk factors for CVD [23,24].…”
Section: Discussionmentioning
confidence: 99%
“…Analyzing the percentile distribution showed that, for FM-tr, the 25th to 75th percentile range was higher in women than in men up to 30–39 years of age (being 3.3–9.6 kg for men in their thirties and 5.3–10.4 kg for women), while there were no substantial differences between the genders in older age. The differences in younger people may be related to the two genders’ physiological hormone profile since the FM-tr values became similar at around the age when women go into menopause, after which the hormone differences between the genders are less pronounced [22]. …”
Section: Discussionmentioning
confidence: 99%
“…For example, a cross-sectional study with a sample of 617 women from southern Brazil observed that women with a history of three or more pregnancies and menarche at the age of 11 or earlier had a 25% higher prevalence of AO compared to nulliparous or primiparous women with menarche at 14 years or older [31]. Studies show that the number of parturitions leads to a tendency of decreased hip circumference and increased WC [37][38][39].…”
Section: Prevalence Of Abdominal Obesitymentioning
confidence: 99%
“…The research with dataset from the Japan Public Health Center Study, which includes a total of 65,095 Japanese aged between 40 and 69 years at baseline has shown that over 10-year follow-up, BMI increases less than 1.0 kg/m 2 among 40 -49 years old and decreases by a similar amount among those 55 and older at baseline [22] [23]. Besides, the First National Health and Nutrition Examination Survey Epidemiologic Follow-up Study has shown mean 10-year change in BMI among men and women by age [24].…”
Section: Discussionmentioning
confidence: 99%